ChemInform Abstract: Access to the 2H‐Tetrahydro‐4, 6‐dioxo‐1, 2‐oxazine Ring System from Nitrone via a Tandem Nucleophilic Addition and Transesterification Reaction. Issue 25 (June 2016) - Yang, Shaoqiang; Liao, Daohong; Tian, Xiaoqi; Lei, Xiaoguang
Abstract: The first general route to the title oxazine ring system, a heterocyclic scaffold found in the complex natural products alchivemycin A and B, is given.